JOB AFFILIATION AND ITS RELATIONSHIP TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF EMPLOYEES IN NATIONAL DEPARTMENTS FOR SPORTS TALENT CARE IN THE CENTRAL AND SOUTHERN REGIONS - Asst. Prof. Dr. Abdul-Hussein Majid Muhammad (Proximus Journal Publishing, 2024)
This investigation intended to create a metric for the degree to which employees in national departments devoted to sports talent are engaged in citizenship behavior towards their organizations, create a metric for the degree to which employees in national departments dedicated to sports talent are associated with their organizations, and determine the association between citizenship behavior and affiliation with organizations of employees in national departments devoted to sports talent in the central and southern regions. The researcher employed the descriptive approach that involved surveys and correlative relationships. The community dedicated to research includes employees of the national organizations that care for athletic talent in the central and southern regions. Their collective has a number of (141) employees. The researcher chose them by the intended method. The sample of the experimental exploration had (10) participants. In the governorship's talent care initiatives from Karbala, they were selected by purpose, the building sample included (100) national employees in the talent care initiatives of Karbala. The investigator suggested that the national departments of sports should be given advantages and benefits for their technical supervisors, and that they should also engage in positive competition with each other in order to promote the country's functional affiliation.
Keywords: Job Affiliation; Organizational Citizenship Behaviorm